(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
In 1953 in Aix-en-Provence, later in Dubrovnik (1956) and up to the epilogue in Otterlo (1959), the youngest generation associated with the CIAM began to question the functionalist categories of the Athens Charter, beginning with the delicate theme of public space. Despite the rightings to the course introduced by the old guard, to overcome the abstract nature of the functional city, Team 10 (in particular the Smithsons and van Eyck) presented an urban environment more adapted to the emotive and material needs of mankind. They invoked a complex spatial model with multiple relations between architectural forms and the social and psychological needs of its users. The disciplinary pluralism of Team 10â€™s approach would later emerge above all in the work of van Eyck, entirely dedicated to the search for a locally suitable form, through â€œanthropological experienceâ€. Speaking at the CIAM in Otterlo (1959) Aldo van Eyck stated: Â«Man is always and everywhere essentially the same. He has the same mental equipment though he uses it differently according to the particular pattern of life of which he happens to be a part. Modern architects have been harping continually on what is different in our time to such an extent that even they have lost touch with what is not different, with what is always essentially the sameÂ». In 1998 Rem Koolhaas created AMO, the other face of the Office for Metropolitan Architecture. AMO is a multidisciplinary research laboratory that works beyond the confines of traditional architecture in order to â€œfertilize itâ€. Koolhaasâ€™ think tank is substantially a tool for understanding the dynamics of contemporary society, the new â€œpublicâ€, based on the conviction that bigness has definitively broken with the functionalist rules of Modernism. What emerges is a certain multidisciplinarity in the work of Koolhaas, which attributes the role of â€œmediatorâ€ to the figure of the architect, called on to interact with experts from different though complementary disciplines in the field of design. On many occasions, the Dutch architect has illustrated the complex relationship between democracy and architecture, representing the evolution of the concept of â€œpublic powerâ€ during the post-war era. If we exclude the private villas, the buildings for private clients and the Prada catwalks, almost all of OMA-AMOâ€™s work confronts contemporary public space, at a range of scales. In 2014 the Museo Nacional Centro de Arte Reina Sofia in Madrid organised an important exhibition entitled Playgrounds. Reinventing the Square, shedding light once again on the playground strategy as a form of interaction between public space-inhabitants, in a collective and shared dimension. The show presented the utopias and realties designed from the mid-twentieth century onward, including the work of Aldo van Eyck who, during the â€œGlorious Thirtyâ€ designed hundreds of public playgrounds in Amsterdam, restoring life and quality to the streets of a city devastated by the Second World War.